Curcumin and Extract of Plantago major, L Increased SPF Value of Cold Cream Base - Sugihartini, Nining (Indonesian Research Gateway, 2010)
Octyl methoxycinnamate as the active material of the sunscreen would be degradated after being exposed to the sunlight. Curcumin, rice flour and theÃÂ extract ofÃÂ PlantagoÃÂ major, L was the material that could function as the sunscreen. The aim of this research was to know the SPF value and the physical characteristics of cream ofÃÂ the sunscreen with the active material octyl methoxycinnamate after the addition of the optimum composition of curcumin and the extract of Plantago major, L and the optimum composition of rice flour and the extract of Plantago major, L. In this research three formulas was examined, i.e. theÃÂ formula I with the active material octyl methoxycinnamate, the formula II with the active material octyl methoxycinnamateÃÂ and the optimum composition curcumin and the extract ofÃÂ PlantagoÃÂ major, L, Formula III with the active material octyl methoxycinnamate and the optimum composition rice flour and the extract of Plantago major, L. SPF value of each formula was determined by using the Petro method (1981) using UV spectrofotometric method at aÃÂ ÃÂ» 290 nm-320 nm. The physical characteristics i.e. the power spread, the adhesiveness and the viscosity were also examined analysed with Anova one way at a confidence levelÃÂ 95%. Result of the research show that SPF value increased after the addition of the optimum composition of curcumin and the extract of Plantago major, L. The physical characteristics of cream of the sunscreen do not change after the addition of the optimum composition curcumin and the extract ofÃÂ Plantago major, L and the optimum composition rice flour and the extract of Plantago major, L.ÃÂ